A Flexible Binding Site Architecture Provides New Insights into CcpA Global Regulation in Gram-Positive Bacteria - Yunpeng Yang (American Society for Microbiology, 2017)
ABSTRACT Catabolite control protein A (CcpA) is the master regulator in Gram-positive bacteria that mediates carbon catabolite repression (CCR) and carbon catabolite activation (CCA), two fundamental regulatory mechanisms that enable competitive advantages in carbon catabolism. It is generally regarded that CcpA exerts its regulatory role by binding to a typical 14- to 16-nucleotide (nt) consensus site that is called a catabolite response element (cre) within the target regions. However, here we report a previously unknown noncanonical flexible architecture of the CcpA-binding site in solventogenic clostridia, providing new mechanistic insights into catabolite regulation. This novel CcpA-binding site, named crevar, has a unique architecture that consists of two inverted repeats and an intervening spacer, all of which are variable in nucleotide composition and length, except for a 6-bp core palindromic sequence (TGTAAA/TTTACA). It was found that the length of the intervening spacer of crevar can affect CcpA binding affinity, and moreover, the core palindromic sequence of crevar is the key structure for regulation. Such a variable architecture of crevar shows potential importance for CcpA’s diverse and fine regulation. A total of 103 potential crevar sites were discovered in solventogenic Clostridium acetobutylicum, of which 42 sites were picked out for electrophoretic mobility shift assays (EMSAs), and 30 sites were confirmed to be bound by CcpA. These 30 crevar sites are associated with 27 genes involved in many important pathways. Also of significance, the crevar sites are found to be widespread and function in a great number of taxonomically different Gram-positive bacteria, including pathogens, suggesting their global role in Gram-positive bacteria. IMPORTANCE In Gram-positive bacteria, the global regulator CcpA controls a large number of important physiological and metabolic processes. Although a typical consensus CcpA-binding site, cre, has been identified, it remains poorly explored for the diversity of CcpA-mediated catabolite regulation. Here, we discovered a novel flexible CcpA-binding site architecture (crevar) that is highly variable in both length and base composition but follows certain principles, providing new insights into how CcpA can differentially recognize a variety of target genes to form a complicated regulatory network. A comprehensive search further revealed the wide distribution of crevar sites in Gram-positive bacteria, indicating it may have a universal function. This finding is the first to characterize such a highly flexible transcription factor-binding site architecture, which would be valuable for deeper understanding of CcpA-mediated global catabolite regulation in bacteria.